O perfil democrático dos Ministérios Públicos Estaduais - Alencar, Manoel Pereira de (2002)
This master's thesis leans on the demand of the current democratic profile of the Brazilian ministerial body , especially with regard to the State Public Prosecutor , since, before, was , in most cases , mere appendage of the executive branch , which came to height of appointment of ad hoc prosecutors to one and only one, being the accusers in the criminal process , not actually participating in the procedural relationship itself, being considered " disposable" by the judiciary , which did not recognize you with the greatness that has always characterized .